Research Trends in Halal Certification and Labeling: Bibliometric Analysis and Systematic Literature Review - Azis, Saipul; Hulwati, Hulwati; Duhriah, Duhriah; Novia, Aidil (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2024)
Indonesia as a country with a Muslim majority makes halal not only a religious principle, but also a significant economic driver. Halal products are no longer just a preference, but a necessity for the majority of consumers in Indonesia. This study aims to see the research trend on halal certification and labeling with bibliometric analysis and systematic literature review. This type of research uses a combined qualitative and quantitative approach in the form of bibliometric analysis, as well as a systematic literature review (SLR) related to halal certification and labeling. Quantitative and qualitative approaches are used using Google Scholar data with a time span of 2015-2023 with the keywords